Severe acute interstitial nephritis after combination immune-checkpoint inhibitor therapy for metastatic melanoma - Murakami, Naoka (Clin Kidney J, 2016)
Immune-checkpoint inhibitors are emerging as revolutionary drugs for certain malignancies. However, blocking the co-inhibitory signals may lead to immune-related adverse events, mainly in the spectrum of autoimmune diseases including colitis, endocrinopathies and nephritis. Here, we report a case of a 75-year-old man with metastatic malignant melanoma treated with a combination of nivolumab (anti-PD1-antibody) and ipilimumab (anti-CTLA-4 antibody) who developed systemic rash along with severe acute tubulointerstitial nephritis after two doses of combination therapy. Kidney biopsy and peripheral blood immune profile revealed highly proliferative and cytotoxic T cell features. Herein, we discuss the pathophysiology and management of immune checkpoint blockade-related adverse events.